Pemidanaan Berbasis Risiko dalam Tindak Pidana Persaingan Usaha Tidak Sehat - Sylvia Paramitha Syahrul; Rudi Suryadi; Endang Bunyamin; Supri Yanto; Nasrullah, Nasrullah (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
Unfair business competition crimes are a form of economic crime that has a systemic impact on the business climate and consumer welfare. Until now, the approach to punishing violations of business competition principles has tended to be symbolic and does not reflect the complexity and risk of losses incurred. This article proposes a risk-based punishment approach as a new framework for determining more proportional and effective criminal sanctions. This approach measures the degree of fault based on the potential for market damage, the level of repetition, and the macroeconomic impact. This study uses a normative method with a legislative and comparative approach to models in the European Union and South Korea. The results of the study show that a risk-based punishment system can increase the deterrent effect on economic criminals and strengthen the legitimacy of criminal law as an instrument of market protection.